Influence of the rotation angles on the mechanical behavior of the one reci instrument - Renaud Giess; Éric Mortier; Marie Delanoë; Romain Hocquel; Jean-Marc Martrette; Rémy Balthazard; Marin Vincent (BDJ Open)
Abstract Aims The reciprocity is a complex endodontic kinematic involving many parameters. The most important of these is undoubtedly the selection of clockwise and counterclockwise rotation angles. In this context, the aim of this study was to determine the influence of clockwise and counterclockwise rotation angles on the mechanical properties of 25/0.06 One Reci reciprocity instruments. Method For this purpose, 5 groups of 10 25/0.06 One Reci instruments were used and each group was associated with a pair of counterclockwise/clockwise rotation angles (CCW/CW). In order to study only one variable at a time, one of the two angles was fixed and the second was increased or decreased. The distribution of angles was as follows: Group 1: 170°/60°; Group 2: 150°/60°; Group 3: 170°/30°; Group 4: 170°/90°; Group 5: 210°/60°. Thanks to a load/unload endodontic protocol carried out on a tensile bench, we quantified for each tested pair of angles (i) the cutting efficiency, (ii) the screwing effect and (iii) the generated torque. Results Increasing or decreasing one of the two rotation angles influences the mechanical behavior of the instruments, as does the resulting range. Therefore, our results showed a direct influence of rotation angles on the mechanical behavior of endodontic instruments. Conclusion This study analyzes the influence of clockwise and counterclockwise rotation angles on the mechanical properties of 25/0.06 One Reci reciprocity instruments. The results of this work tend to demonstrate a direct influence of rotation angles on the mechanical behavior of 25/0.06 One Reci instruments.